Daydreaming and grandiose delusions: development of the qualities of daydreaming scale - Isham, L (Cambridge University Press, 2024)
Background: Daydreaming may contribute to the maintenance of grandiose delusions. Repeated, pleasant, and vivid daydreams about the content of grandiose delusions may keep the ideas in mind, elaborate the details, and increase the degree of conviction in the delusion. Pleasant daydreams more generally could contribute to elevated mood which may influence the delusion content.